Resilience and self-efficacy beliefs: A study of immigrant adolescents - Μόττη-Στεφανίδη, Φρόσω; Παυλόπουλος, Βασίλης; Τάκης, Νίκος; Ντάλλα, Μαρίνα; Παπαθανασίου, Αθανασία Χρυσούλα; Masten, Ann S. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF